Micropatterning of TCR and LFA-1 ligands reveals complementary effects on cytoskeleton mechanics in T-cells - Tabdanov, Erdem (Integr Biol (Camb), 2015)
The formation of the immunological synapse between a T-cell and the antigen-presenting cell (APC) is critically dependent on actin dynamics, downstream of T-cell receptor (TCR) and integrin (LFA-1) signalling. There is also accumulating evidence that mechanical forces, generated by actin polymerization and/or myosin contractility regulate T-cell signalling. Because both receptor pathways are intertwined, their contributions towards the cytoskeletal organization remain elusive. Here, we identify the specific roles of TCR and LFA-1 by using a combination of micropatterning to spatially separate signalling systems and nanopillar arrays for high-precision analysis of cellular forces. We identify that Arp2/3 acts downstream of TCRs to nucleate dense actin foci but propagation of the network requires LFA-1 and the formin FHOD1. LFA-1 adhesion enhances actomyosin forces, which in turn modulate actin assembly downstream of the TCR. Together our data shows a mechanically cooperative system through which ligands presented by an APC modulate T-cell activation.